Comparison of Outcomes Between McKeown and Sweet Esophagectomy in the Elderly Patients for Esophageal Squamous Cell Carcinoma: A Propensity Score-Matched Analysis - Chen, Dongni; Hu, Yihuai; Chen, Youfang; Hu, Jia; Wen, Zhesheng (Cancer control, 2020)
The aim of this study was to compare the perioperative outcomes and long-term survival rates of the McKeown and Sweet procedures in patients with esophageal cancer younger than 70 years or older than 70 years. A total of 1432 consecutive patients with esophageal squamous cell carcinoma (ESCC) who received surgery at Sun Yat-sen University Cancer Center from January 2009 to October 2012 were analyzed. Propensity score matching was used to balance the clinical characteristics of the patients who underwent different surgical approaches, and 275 and 71 paired cases were matched among those younger and older than 70 years, respectively. The prognosis and postoperative outcomes were compared between the McKeown and the Sweet esophagectomy. For patients younger than 70 years, those who underwent the McKeown procedure had better overall survival (OS) than those in the Sweet group (log rank = 4.467; P = .035). However, no significant difference in disease-free survival and OS was observed between two approaches for the elderly patients (log rank = 1.562; P = .211 and log rank = 0.668; P = .414, respectively). Cox regression analysis revealed that McKeown approach was a positive prognostic factor compared to the Sweet approach for patients younger than 70 years in univariable analysis (HR = 0.790; 95% CI, 0.625-0.997; P = .047), whereas the surgical approach was not significantly related to the prognosis in the elderly patients. For patients older than 70 years, the occurrence of anastomotic fistula increased in those who underwent the McKeown procedure (23.9% vs 11.3%, P = .038, for the McKeown and Sweet esophagectomy, respectively). The McKeown approach increases the OS in younger patients with ESCC. However, for patients older than 70 years, the Sweet approach was proven to be an effective therapy, given the better perioperative outcomes and similar long-term survival compared with patients in the McKeown group.